Efficacy of early initiation of breastfeeding (EIB) for preventing hypothermia in newborns - Muthoharoh, Binti Lu'lu'; Yuriah, Siti; Gustiani, Ria; Agustina, Yaolanda Rizqi; Indrawati, Indrawati; Mufdlilah, Mufdlilah (Universitas Aisyiyah Yogyakarta, 2022)
Newborns are at risk of losing body heat after birth. According to UNICEF, the global infant mortality rate is still worrying, in Sub-Saharan Africa, of 29 deaths per 1,000 births. It means that 80% of deaths are caused by asphyxia, complications at birth, hypothermia, and sepsis. In Indonesia, the causes of death for newborns 0-6 days include respiratory disorders (36.9%), prematurity (32.4%), sepsis (12%), hypothermia (6.8%,) and jaundice (6.6%). Evidence suggests some technological interventions in preventing hypothermia in newborns, such as skin-to-skin contact between mother and baby. This study aimed to explore available technological evidence regarding the effectiveness of IMD in the prevention of hypothermia in newborns. The review is based on the integrative review method by following the modified design it consists of identifying topics, identifying problems/questions, collecting data with relevant evidence, evaluating data, analyzing, and interpreting data, concluding, and presenting results. PRISMA flow diagram is used to show the flow of evidence search. The results of the review included 10 articles. From the review, three facts were discovered, namely, EIB can increase temperature, increase breastfeeding levels, and increase low weight loss in the baby's first days. Infant mortality can be prevented with the role of trained health workers during ANC, delivery/postnatal, and EIB during the first/two hours of postpartum to prevent hypothermia.